Dopamine-intercalated polyelectrolyte multilayered nanofiltration membranes: toward high permselectivity and ion-ion selectivity - Yang, Yang (2022)
The layer-by-layer (LbL) self-assembly is a common method for fabricating nanofiltration (NF) membranes. However, most multilayers are usually too thick and lack the necessary attributes to endow NF membranes with good permselectivity. In this study, we present a polyelectrolyte multilayered method by integrating dopamine as a “bio-glue”. A three-step deposition was applied to the negatively charged PES substrate surface, following an alternate sequence of poly(allylamine hydrochloride) (PAH), dopamine (DA) and poly(sodium 4-styrenesulfonate) (PSS). The dopamine molecules were intercalated between the PAH and PSS layers to achieve a thinner thickness, higher hydrophilicity, smaller surface roughness and narrower pore size distribution. The resultant flat sheet (PAH/DA/PSS)4 polyelectrolyte multilayered (PEM) membranes exhibited enhanced water permeability (more than 60% increment from 13.5 to 21.9 LMH/bar) and higher rejection toward divalent ions (increasing MgCl2 rejection from 91.0% to 94.8%) as compared with the control (PAH/PSS)4 NF membrane. Furthermore, the developed LbL method was applied on hollow fiber membrane modules and was able to achieve a higher Li+/Mg2+ selectivity from 15.6 to 37.8 and Na+/Mg2+selectivity from 11.0 to 19.1 using different simulated brines as feed solutions. On the whole, this polyelectrolyte multilayered method shows great potential for practical applications, including groundwater softening, seawater pretreatment and lithium extraction.